2016
DOI: 10.1007/s00436-016-5177-0
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response relationship in Schistosoma mansoni juvenile and adult stages following limonin treatment in experimentally infected mice

Abstract: Preventive chemotherapy with praziquantel is the mainstay of schistosomiasis control. However, drug resistance is an imminent threat, particularly with large-scale administration of praziquantel, in addition to much less efficacy against young schistosomes. Several biological activities of limonin have been explored such as insecticidal, insect antifeedant, and growth-regulating activity on insects as well as antimalarial, antiviral, anticancer, cholesterol-lowering, and antioxidant activities. This study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Oral administration of limonin to S. mansoni experimentally infected mice resulted in worm burden reduction and significant reductions in both hepatic and intestinal tissue egg loads with elevated dead egg levels. Limonin also produced reduction in dimensions and number of hepatic granulomas [39] . In the present study, we investigated the in vitro schistosomicidal activity of pure limonin compound against adult S. mansoni worms.…”
Section: Discussionmentioning
confidence: 90%
“…Oral administration of limonin to S. mansoni experimentally infected mice resulted in worm burden reduction and significant reductions in both hepatic and intestinal tissue egg loads with elevated dead egg levels. Limonin also produced reduction in dimensions and number of hepatic granulomas [39] . In the present study, we investigated the in vitro schistosomicidal activity of pure limonin compound against adult S. mansoni worms.…”
Section: Discussionmentioning
confidence: 90%
“…Besides the antischistosomal activity, it has been demonstrated that antioxidants are capable of restoring the activity of antioxidant liver enzymes near to the levels detected on controls [107,109,117,119,126,[129][130][131]. The increase of antioxidant enzymes activity is usually accompanied by reduction on granuloma size and number, resulting in improvement of the liver architecture and functions [108,125,128,129,132,133].…”
Section: Schistosomiasismentioning
confidence: 99%
“…In addition, they support internal organs including the reproductive, excretory and digestive tracts, and maintenance of the female within the gynecophoral canal of the male [121,122]. It was also observed that antioxidants are capable of inducing severe tegumental alterations [108,111,117,120], which is a crucial organ for protection against host responses, nutrient uptake for parasite development and growth, and plays an important role in host-parasite interaction [123]. Moreover, antioxidants impaired worm coupling [113,114,116,124], a process fundamental to oviposition [107,120,[125][126][127][128].…”
Section: Schistosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, studies evaluating efficacy of antioxidants, alone or concurrently with antischistosomal drugs targeting not only parasite but also pathologies associated to infection have been reported [ 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 , 140 ] ( Table 1 and Figure 5 ).…”
Section: Antioxidants: a New Chemotherapy Against Schistosomiasis?mentioning
confidence: 99%